1992
DOI: 10.1159/000315541
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Parahippocampal Somatostatin 28 and Neuropeptide Y Containing Neurons in Alzheimer's Disease (Part 2 of 2)

Abstract: The somatostatinergic innervation, and by comparison that of neuropeptide Y, was examined by immunocytochemistry, in the hippocampal formation of 6 patients with clinically and neuropathologically confirmed diagnosis of Alzheimer's disease (AD) and 4 matched controls. The quantitative assessment of the somatostatin and neuropeptide Y immunoreactive cell perikarya was conducted on regularly spaced sections covering the span of the whole hippocampus and parahippocampal cortex. The estimated total number of somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Most consistent changes have been reported in corticotrophin releasing factor (DeSouza et al 1986;Whitehouse et al 1987), and somatostatin (somatotropin release-inhibiting factor, SRIF) [reviewed by Bissette & Myers 1992;Cervera-Pierot et al 1992). …”
Section: Deficits Of Peptidergic Neurotransmissionmentioning
confidence: 79%
“…Most consistent changes have been reported in corticotrophin releasing factor (DeSouza et al 1986;Whitehouse et al 1987), and somatostatin (somatotropin release-inhibiting factor, SRIF) [reviewed by Bissette & Myers 1992;Cervera-Pierot et al 1992). …”
Section: Deficits Of Peptidergic Neurotransmissionmentioning
confidence: 79%
“…Pathological changes in the white matter could interfere with the connections among somatostatinergic cortical intemeurons affecting somatostatinergic fibers. Another possible explanation is that direct damage to the white matter of the hippocampal cortex, one of the major foci of somatostatinergic activity, leads to decreased levels of SLI [50][51][52][53], Some SDAT studies reported a specific cell loss of somatostatin-immunoreactive perikarya and axons whereas in others somatostatin-immunoreactive peri karya number was preserved and only the density of somatostatin-immunoreactive fibers was altered. These discrepancies suggest that modifications of somatostatin CSF o f SLI, HVA and 5-HIAA in Binswanger's and A lzheim er's Disease levels might result from altered mechanisms occurring at the transcriptional and/or posttranscriptional level [52].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining of mounted sections (12 µm) was carried out with purified anti-Rxt1 antibodies (1:1,000 dilution; overnight incubation at room temperature) as already described (Cervera-Pierrot et al, 1992).…”
Section: Immunoautoradiographic and Light Microscope Immunohistochemimentioning
confidence: 99%